Effects of prior concentric training on eccentric exercise induced muscle damage - Gleeson, N.; Eston, R.; Marginson, V.; McHugh, M. (British Journal of Sports Medicine, 2003)
Background: Exercise induced muscle damage (EIMD) from strenuous unaccustomed eccentric exercise is well documented. So too is the observation that a prior bout of eccentric exercise reduces the severity of symptoms of EIMD. This has been attributed to an increase in sarcomeres in series. Recent studies have suggested that prior concentric training increases the susceptibility of muscle to EIMD following eccentric exercise. This has been attributed to a reduction of sarcomeres in series, which decreases muscle compliance and changes the length-tension relation of muscle contraction.